Primary and secondary pyroelectric effects of ferroelectric 0-3 composites - Chew, Khian Hooi; Choy, C.L.; Shin, F.G.; Ploss, B.; Chan, H.L.W. (2003)
Simple and tractable analytical expressions for determining the pyroelectricity in ferroelectric 0-3 composites have been developed. For the dilute suspension limit, expressions for the effective pyroelectric and other thermal electromechanical properties are derived within the framework of the Maxwell-Wagner approach. Then, an effective-medium theory is employed to examine the first and second pyroelectric coefficients in the concentrated suspension regime. The effective-medium approach as compared to the Maxwell-Wagner approach results in a better agreement with known experimental data up to higher volume fraction of inclusions. The pyroelectricity of 0-3 composites of ceramic inclusions embedded in the P(VDF-TrFE) copolymer matrix and of P(VDF-TrFE) inclusions embedded in a ceramic matrix are analyzed numerically under different polarization configurations. The theoretical predictions show that the secondary pyroelectric effects in composite systems with ceramic as the matrix are stronger than those with the copolymer as the matrix and can sometimes dominate the pyroelectricity for certain compositions. (C) 2003 American Institute of Physics.